2017
DOI: 10.1371/journal.pone.0175978
|View full text |Cite
|
Sign up to set email alerts
|

Assessing environmental attributes and effects of climate change on Sphagnum peatland distributions in North America using single- and multi-species models

Abstract: The fate of Northern peatlands under climate change is important because of their contribution to global carbon (C) storage. Peatlands are maintained via greater plant productivity (especially of Sphagnum species) than decomposition, and the processes involved are strongly mediated by climate. Although some studies predict that warming will relax constraints on decomposition, leading to decreased C sequestration, others predict increases in productivity and thus increases in C sequestration. We explored the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 67 publications
6
26
0
1
Order By: Relevance
“…As expected, the total suitable area reduced in the future climate scenarios, especially in RCP8.5, which suggested that global warming would hinder the development of Sphagnum bogs seriously. Conversely, the different conclusion was drawn in North America [41]. The reason, as described by Gunnarsson, might be that climatic parameters together with geographical position are important for Sphagnum bogs.…”
Section: Discussionmentioning
confidence: 96%
“…As expected, the total suitable area reduced in the future climate scenarios, especially in RCP8.5, which suggested that global warming would hinder the development of Sphagnum bogs seriously. Conversely, the different conclusion was drawn in North America [41]. The reason, as described by Gunnarsson, might be that climatic parameters together with geographical position are important for Sphagnum bogs.…”
Section: Discussionmentioning
confidence: 96%
“…S. fuscum exhibits an efficient retention of moisture, due to its dense growth form, and therefore microforms dominated by these species may be less vulnerable to drying and deep burning than other Sphagnum species (Benscoter & Wieder, ). Combining species distribution models and climate projections, Oke and Hager () showed S. fuscum growth potential may remain stable in central‐northern Alberta until 2050 CE. Other studies suggested persisting large‐scale drying of peatlands of this region during the 21st century may eventually cause an increase in net CO 2 emissions (Cai, Flanagan, & Syed, ) and this effect may become stronger in case Sphagnum is replaced by shrubs (Munir, Xu, Perkins, & Strack, ), a trend which was observed in the upper sections of JPH4 and ANZ (Magnan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…S. fuscum exhibits an efficient retention of moisture, due to its dense growth form, and therefore microforms dominated by these species may be less vulnerable to drying and deep burning than other Sphagnum species (Benscoter & Wieder, 2003). Combining species distribution models and climate projections, Oke and Hager (2017) showed S. fuscum growth potential may remain stable in central-northern Alberta until 2050 CE.…”
Section: Th-century Environmental Changementioning
confidence: 99%
“…Our To project the future extent of peatlands, bioclimatic envelope models and ecological niche models have been used. Oke and Hager (2017) predicted that the areas of suitable climate in North America for Sphagnum peatland should increase in the future up to 2050.…”
Section: Impact Of Peatlands On Northern Terrestrial Carbon Balancementioning
confidence: 99%